Evaluating environmental effects on the structural behavior of the railroad track subgrade considering different sub-ballast design solutions. (May 2022) - Castro, G.; Pires, J.; Motta, R.; Bernucci, L.; Fortunato, E.; Futai, M.
Abstract: The subgrade of a freight railroad track must have sufficient bearing capacity to prevent excessive plastic strains and geometry-related problems to ensure its good performance. The track sub-ballast layer is used to distribute the loads from the ballast to the subgrade, as well as to mitigate climate-based subgrade problems. This study aims to evaluate the effects of Brazilian southeastern tropical climate on subgrade hydraulic and structural behavior, as well as its effect on the railroad track substructure. This is achieved by considering both granular and bituminous sub-ballast solutions. Accordingly, suction sensors were installed at the subgrade for the real-time monitoring and calibration of both track sections. The subgrade water retention was characterized by considering the effect of hydraulic hysteresis. Two independent finite element method (FEM) numerical models were developed. Water flow analyses were performed using a 2-D model to obtain the suction variation in the track substructure profile using climate-track interaction simulations. A 3-D model was used to evaluate the railroad track structural behavior in terms of wheel load–track (interaction simulations) displacement, stress, and strain. Hence, it was possible to calculate the subgrade resilient modulus using a constitutive model considering different hydraulic conditions obtained from a 2-D model and in-track monitoring. The results show that both the groundwater level and climate are crucial for evaluating the subgrade structural behavior, track design, and maintenance work. Suction variation and the hysteresis effect on subgrade hydraulic characterization significantly affect the resilient modulus and track performance of the subgrade. Bituminous sub-ballast proved to be more efficient than granular sub-ballast, as revealed by service life-cycle predictions.